The use of augmented reality for inquiry-based activity about the phenomenon of seasons: effect on mental effort and learning outcomes - Martin, Elena; Castéra, Jérémy; Cheneval-Armand, Hélène; Brandt-Pomares, Pascale (Frontiers in Education, 2023)
Despite the profusion of studies on the use of augmented reality (AR) for teaching, the scientific results on the students' learning do not fully converge. On the one hand, some studies have shown AR's benefits, including autonomy and improvement of learning by reducing mental effort. On the other hand, other studies have highlighted the strong limitations of AR technology for learning, such as cognitive over loading in some specific cases. This study investigates the impact of AR on the mental effort and learning outcomes of students who were involved in an inquiry-based science training session. The sample was composed of French Master's degree students. A control group who used physical modelling activities and an experimental group who used an AR model for the first time studied the phenomenon of the seasons. The students were tested on their learning outcomes and mental effort during the training session. Results revealed no significant differences, except for the short-term test which showed better learning results for the control group. Moreover, a link between mental effort and learning outcomes was observed independently of the group conditions. Despite the first use of an AR model to study a complex scientific phenomenon, the experimental group (AR) performs in similar way to the control group (without AR) in long-term learning outcomes and mental effort.